A Digital Twin Powered Aerial Link Orchestration using SDRs - Bayram, Busra; Secinti, Gokhan (IEEE World Forum on Internet of Things, 2024)
The structures and dynamic working environments of drones indicate that the networks they create are subject to dynamic conditions, making it important to maintain continuous and high-quality communication. Communication quality is obviously influenced not only by the environment in which the drone operates (such as weather conditions) but also by its overall architecture and flight parameters. In this paper, we propose a novel methodology to enhance inter-drone communication quality. We validate our methodology by running tests on our comprehensive testbed, demonstrating the method's effectiveness. Furthermore, we extend our methods by applying Digital Twin technology to enhance the Modulation and Coding Scheme (MCS) table. Our approach systematically examines the influence of drone flight parameters on Packet Delivery Ratio (PDR), delving into the intricacies of drone-to-ground control unit communications. Through careful analysis and optimization, we identify key conditions and parameters critical for achieving optimal communication performance. In particular, we demonstrate how SDR-based links can improve the quality of communication between drones and control unit. Our findings show that our proposed approaches improve PDR by 27%. Furthermore, our analysis indicates that drone Hold flying mode is an important element impacting this quality. These results increase our understanding of drone communication systems while also optimizing performance in practical applications.